ARTICLE REVIEW: THE USE OF AROMATHERAPY FOR ANOSMIA PATIENTS DURING THE COVID-19 PANDEMIC - Ali Akbar; Priya Yuga Prasetya (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2022)
This study was conducted to determine the benefits of aromatherapy for anosmia people after exposure to COVID-19. Aromatherapy was often used for health therapy so it has the potential for the treatment of anosmia. This study is necessary to be done because there are a lot of anosmia sufferers and there is no effective way to treat it. The study of post-COVID-19 anosmia continues to evolve and more needs to be researched. This study was conducted by reviewing several literature studies originating from international and national journals, theses, and dissertations with a year limit of the last 10 years. From some literature it is known that aromatherapy can reduce the risk caused by anosmia. Aromatherapy can enter through the body's circulatory system and olfactory system through fragrances, It will affect the condition, memory, and psyche of a person. Although not very effective, further research on the benefits of aromatherapy for people with anosmia is necessary.